The cytological changes of tobacco zygote and proembryo cells induced by beta-glucosyl Yariv reagent suggest the involvement of arabinogalactan proteins in cell division and cell plate formation - Yu, Miao (BioMed Central, 2012)
BACKGROUND: In dicotyledonous plant, the first asymmetric zygotic division and subsequent several cell divisions are crucial for proembryo pattern formation and later embryo development. Arabinogalactan proteins (AGPs) are a family of extensively glycosylated cell surface proteins that are thought to have important roles in various aspects of plant growth and development, including embryogenesis. Previous results from our laboratory show that AGPs are concerned with tobacco egg cell fertilization and zygotic division. However, how AGPs interact with other factors involved in zygotic division and proembryo development remains unknown. RESULTS: In this study, we used the tobacco in vitro zygote culture system and series of meticulous cell biology techniques to investigate the roles of AGPs in zygote and proembryo cell division. For the first time, we examined tobacco proembryo division patterns detailed to every cell division. The bright-field images and statistical results both revealed that with the addition of an exogenous AGPs inhibitor, beta-glucosyl Yariv (beta-GlcY) reagent, the frequency of aberrant division increased remarkably in cultured tobacco zygotes and proembryos, and the cell plate specific locations of AGPs were greatly reduced after beta-GlcY treatment. In addition, the accumulations of new cell wall materials were also significantly affected by treating with beta-GlcY. Detection of cellulose components by Calcofluor white stain showed that strong fluorescence was located in the newly formed wall of daughter cells after the zygotic division of in vivo samples and the control samples from in vitro culture without beta-GlcY treatment; while there was only weak fluorescence in the newly formed cell walls with beta-GlcY treatment. Immunocytochemistry examination with JIM5 and JIM7 respectively against the low- and high-esterified pectins displayed that these two pectins located in opposite positions of zygotes and proembryos in vivo and the polarity was not affected by beta-GlcY. Furthermore, FM4-64 staining revealed that endosomes were distributed in the cell plates of proembryos, and the localization pattern was also affected by beta-GlcY treatment. These results were further confirmed by subsequent observation with transmission electron microscopy. Moreover, the changes to proembryo cell-organelles induced by beta-GlcY reagent were also observed using fluorescent dye staining technique. CONCLUSIONS: These results imply that AGPs may not only relate to cell plate position decision, but also to the location of new cell wall components. Correlated with other factors, AGPs further influence the zygotic division and proembryo pattern establishment in tobacco.